Bibliometric Analysis of Corporate Social Responsibility Against Financial Performance (In Manufacturing Companies on the IDX in 2019-2022) - Aini, Nurul Aini (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to map research topics in the field of "Corporate Social Responsibility". Identify several research variations in terms of keywords, definitions, methodological theories, years of publication and research results. As well as providing suggestions for further researchers. This study uses secondary data. The sample used was 40 articles on "Corporate Social Responsibility". Data collection in this study was by direct observation of articles using the bibliometric analysis method using three specific applications of bibliometric analysis, including Mendeley, Publish of Perish, Vosviewer and graphics using Microsoft official excel. This research resulted in mapping the topic of "Corporate social responsibility" through VOSviewer which shows the 5 Cluster mapping. The implications of this mapping result can be used for practitioners who are expected to provide a reference for academics such as students, lecturers or accountants educators who will conduct research using biometric analysis.Keywords: Corporate Social Responsibility, Publish Of Perish, Vosviewer.